Elastomeric patterns probed by a nematic liquid crystal - Trindade, A.C. (2018)
Soft Janus elastomers have two surfaces with diverse characteristics. In this work, by tuning the chemical composition and the surface roughness we were able to vary the wettability of thin films (thickness of 100-200 mu m) and spheres (diameters in the order of 200 mu m to 2 mm) and evidence the multifunction of the opposite sides. We also describe a simple and inexpensive method to reveal the wrinkled-labyrinthine patterns that appear in the Janus particles by means of a nematic liquid crystal (LC). LC contact angle measurements associated with the swelling and anchoring characteristics of the surfaces were used to image the Janus particles opening new platforms for sensor applications from flexible free-standing LCs containers.